Evaluation of Knowledge, Attitude, and Practice about the Rational Use of Medicines among Junior Residents in a Tertiary Hare hospital in India - Sakshi Singh; Arvind K. Yadav; Meenu Pichholiya; Sandeep K. Kamlekar; Sangita Gupta (Universitas Padjadjaran, Indonesia, 2022)
Rational use of medicine is an integral part of the health care system, which has become the weakest part due to various contributors like prescribers, producers, controllers, and consumers that have led to irrationality and increased the patient’s socio-economic burden. This study aimed to assess junior residents’ knowledge, attitude, and practice of rational medicine of medicine in a tertiary care teaching hospital. This cross-sectional observational study was conducted in the Department of Pharmacology at the tertiary care teaching hospital in Rajasthan, India, for a period of six months, from February 2021 to June 2021. All first- and second-year hospital residents, except those unwilling to participate, were included in the study. The first part of the questionnaire was about knowledge, and the second part was about the attitude and practice of junior residents regarding the rational use of medicines. The data was presented in the form of figures and percentages. Most residents (98%) were aware of the term rationality and rational use of medicines. Maximum numbers of residents (97%) were aware of the term essential medicines. The residents who were aware of drugs included in the National Essential of Medicine and term P-drug were 55% and 69%, respectively. Nearly 21% of residents prescribe drugs by generic names, while the majority (65%) prescribe both generic and brand names. Almost all (98%) of residents agreed that regular training is needed about the rational use of medicines to improve rational prescribing and 89% of residents think regular prescription auditing should be done. This study concludes that most residents were aware of the rational use of medicines, essential medicines, and the P drug concept. But they should receive regular training on the rational use of medications. This will prevent serious problems related to the inappropriate prescribing of medicines during their medical practice.